Youtube-based stroke care education development and its effectiveness on the levels of compliance with physical rehabilitation in post-stroke patients - Cahyani, Gita; Rumahorbo, Hotma; Sudirman, Sudirman (Universitas Muhammadiyah Semarang, 2023)
Stroke is damage to brain tissue due to disruption of blood flow to the brain. One impact in stroke patients is weakness on one side of the body or hemiparesis. The management of stroke includes physical rehabilitation. However, many post-stroke patients still do not comply with physical rehabilitation, so education is needed about the importance of complying with physical rehabilitation to accelerate recovery and restore movement function in post-stroke patients. The purpose of this study is to develop Stroke Care Education and analyze its effectiveness on adherence to physical rehabilitation in post-stroke patients. The design of this study used Research and Development (R&D) and a quasy experiment with a pretest-posttest control group design which was carried out for 21 days. The sampling technique used purposive sampling which consisted of 60 respondents who were divided into the intervention and control groups. The intervention group was given YouTube-based Stroke Care Education twice a day (20 minutes), while the control group was given a leaflet. The measurement method used a level of adherence questionnaire, namely the Morinsky Medication Adherence Scale (MMAS) with low, medium, and high measurement values. The data were analyzed using the Wilcoxon test and the Mann-Whitney test. The results of this study YouTube-based Stroke Care Education is suitable for use for post-stroke patients with a validity test result value of 87.5%. The statistical test results showed an increase in adherence to physical rehabilitation in the intervention group compared to the control group, from an average score of 4.40 to 7.57. Meanwhile, in the control group, it increased from 3.77 to 4.23 with a value of p = 0.000. In conclusion, YouTube-based Stroke Care Education is effective in increasing adherence to physical rehabilitation in post-stroke patients.